Optimization of the efficiency of Piezoelectric energy harvesters. - Domingo C. Lising IV, Venice Clei S. Oaper, Alfredo S. Pangilinan III, Neil Bryan G. Simundo. 4 0 16; 5
u
Undergraduate Thesis: (Bachelor of Science in Electronics Engineering) - Pamantasan ng Lungsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2